High-performance deterministic in situ electron-beam lithography enabled by cathodoluminescence spectroscopy. (18th March 2021) - Rodt, S; Reitzenstein, S
Abstract: The application of solid-state quantum emitters in real-world quantum information technologies requires precise nanofabrication platforms with high process yield. Self-assembled semiconductor quantum dots with excellent emission properties have proven to be among the best candidates to meet the needs of a number of novel quantum photonic devices. However, their spatial and spectral positions vary statistically on a scale that is far too large for their system integration via fixed lithography and inflexible processing schemes. We solve this severe problem by introducing a flexible and deterministic manufacturing scheme based on precise and convenient cathodoluminescence spectroscopy followed by high-resolution electron-beam lithography. The basics and application examples of this advanced in situ electron-beam lithography are described in this article. Although we focus here on quantum dots as photon emitters, this nanotechnology concept is very well suited for the fabrication of a variety of quantum nanophotonic devices based on quantum emitters that exhibit suitably strong cathodoluminescence signals.